Socio-environmental gaps in concession processes: PETAR case study - Abreu Nunes, Gabrielle; Pauline Barão Septanil, Moema; Magro-Lindenkamp, Teresa Cristina (Guará Journal, 2023)
Visitor support concessions in Protected Areas (PAs) have been promoted as a strategy to address human and financial resource shortfalls. Among the Brazilian PAs planned for this approach is the Alto do Ribeira State Tourist Park (PETAR). However, experts and local representatives have questioned whether the ongoing concession process considers the needs of the park’s surrounding communities. The group "PETAR without concession" gathered support from various stakeholders to request the due participation of the local and traditional communities of the Ribeira Valley, whose nature-based livelihoods depend directly or indirectly on tourism. This study aimed to identify the level of public participation encouraged in concession planning and understand whether the demands of different stakeholders were considered in the decision-making process. To this end, we qualitatively analyzed the motions and hearings that took place at the municipal and state levels related to the process, verifying the direction of the discourse and the levels of citizen participation proposed by Arnstein (1969). From the data set, it was possible to conclude that the planning process in question can be classified as “top-down” and that the participation of actors affected by community-based tourism was neglected.